Literary therapy and child mental-health advocacy in Clara Ng’s stories - Laila, Wahda Rahma; Ambarwati, Ari (Universitas Ahmad Dahlan, 2025)
C hildren's literature has great potential in supporting children's mental health. However, in Indonesia, the issue of children's mental health is still often considered taboo. This article aims to re-read Clara Ng's collection of stories, Bagai Bumi Berhenti Berputar (As If the Earth Stopped Spinning), as a form of advocacy for children experiencing mental health issues through a therapeutic approach to literature. This study uses a descriptive qualitative method with empathetic narrative reading techniques on five children's stories, namely Pohon Harapan, Seribu Sahabat Selamanya, Kerlip Bintang di Langit, Jangan Lupa Aku Mencintaimu, and Yang Paling Istimewa. The analysis was conducted in three stages: (1) identifying the emotional conflicts and inner dynamics of the child characters, (2) interpreting the symbolism and coping mechanisms that appear in the narrative, and (3) examining the forms of emotional advocacy built through the relationships between characters and the storytelling structure. The results of the study show that these stories: (a) validate children's emotions honestly without denial, (b) provide an emotional safe space through symbols, dialogue, and imagination that enable reflection and recovery, and (c) strengthen children's agency in dealing with traumatic experiences by attaching meaning to emotional experiences. In conclusion, this collection of stories not only represents children's psychological dynamics but also functions as a medium of literary advocacy that supports emotional recovery and encourages the surrounding environment to be more sensitive to children's mental health issues.